When is a subsea anchor required for a short pipeline/SCR system?. (March 2019) - Reda, Ahmed; McKee, Kristoffer K.; Howard, Ian M.; Sultan, Ibrahim A.
Abstract: Connection of floating production vessels to subsea pipelines requires careful consideration of the stresses placed on the steel catenary riser (SCR), subsea spool and pipeline end termination (PLET). Due to vessel motion, environmental conditions, flow conditions and pipeline temperature gradients during start-up/shut-down and operation, the forces on all sections of the subsea pipeline system may deviate from their static configurations. Pipeline risers, PLETs and spools have design limits that must not be exceeded in order to ensure the integrity of the pipeline/SCR system. The operational/dynamic loads on the pipeline/SCR system cause expansion and contraction of the pipeline at the riser and free end locations, and these also need to be kept within the pipeline system design limits. The most appropriate method to account for the pipeline system movement is to ensure the pipeline has sufficiently long run-out to accommodate the pipeline system loading or to provide anchoring locations for the pipeline section. This paper addresses, with examples and calculations, the criteria that must be considered during the design of the pipeline/SCR system to determine if hold-back anchors are needed and their optimum locations in the system. The criteria for the anchoring are valid for short pipelines with route bend and no lateral buckling. Highlights: Addresses the criteria to determine requirement for anchoring a short pipeline connected to a SCR in the absence of lateral buckling. Discusses the potential methods available to anchor the pipeline and limit the axial feed-in towards the SCR. Provides insights into the driving walking mechanisms of a pipeline connecting to a SCR. Highlights the risks associated with the lateral ratcheting of a route bend.